Persepsi Masyarakat Nelayan Sondong Terhadap Alat Tangkap Sondong di Daerah Sungsang Banyasin Sumatera Selatan - Helfa Septinar; Yunita Panca Putri; Ita Emilia; Rita Puspasari (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2025)
fisheries are the mainstay of the coastal community's economy, and Sondong fishing gear is still commonly used. Although Sondong is considered effective, it raises ecological concerns because it risks damaging the seabed habitat and produces high bycatch. This study aims to describe fishing communities' perceptions of Sondong fishing gear regarding its effectiveness and impact on fish resources and the environment. The study employed a quantitative descriptive approach with purposive sampling of active fishermen in Sungsang, conducted in November 2024. The results show that fishermen have a strong understanding of Sondong because it has been widely used and passed down informally. They perceive Sondong as an effective and profitable tool, though this perception is changing as catches decline. The ecological impact has not been widely recognized, and regulations tend to be rejected due to economic dependence. As fishermen's perceptions are more oriented toward the economy than ecology, an educational approach is needed to encourage the transition to more sustainable fishing gear.